100 greatest American and British animated films - Hischak, Thomas S. (Rowman & Littlefield, 2018)
"A discussion of the 100 most significant animated features produced in the U.S. and the U.K. Each entry includes a synopsis, production history, a summary of the critical response, commentary on the writing, animation, background art, music and/or songs, the voice actors in addition to influence, and so much more"--Provided by publisher.